Improving 3D-Turbo Code's BER Performance with a BICM System over Rayleigh Fading Channel - Yao, R.; Zhu, Y.; Xu, J.; Gao, F.; Wang, L. (Radioengineering, 2016)
Classical Turbo code suffers from high error floor due to its small Minimum Hamming Distance (MHD). Newly-proposed 3D-Turbo code can effectively increase the MHD and achieve a lower error floor by adding a rate-1 post encoder. In 3D-Turbo codes, part of the parity bits from the classical Turbo encoder are further encoded through the post encoder. In this paper, a novel Bit-Interleaved Coded Modulation (BICM) system is proposed by combining rotated mapping Quadrature Amplitude Modulation (QAM) and 3D-Turbo code to improve the Bit Error Rate (BER) performance of 3D-Turbo code over Raleigh fading channel. A key-bit protection scheme and a Two-Dimension (2D) iterative soft demodulating-decoding algorithm are developed for the proposed BICM system. Simulation results show that the proposed system can obtain about 0.8-1.0 dB gain at BER of 10^{-6}, compared with the existing BICM system with Gray mapping QAM.